Pengaruh Penggunaan Mulsa Plastik Terhadap Kelimpahan Serangga Myzus persicae pada Tanaman Cabai Rawit (Capsicum frutescens L.) - KADEK DWI UTAMA; I GUSTI NGURAH BAGUS; I KETUT SIADI; DEWA NYOMAN NYANA; GEDE SUASTIKA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2015)
ABSTRACT Effect of Plastic Mulch to Myzuspersicae Insect Abundance in Plant Cayenne Pepper (Capsicum frutescens L.) Cayenne Pepperis one of theimportantvegetablesgrowncommerciallyinthe tropicsandoccupythe mostextensiveacreageamongother vegetablesin Indonesian. There are fivespeciesarecommonly cultivatedchiliCapsicumannuum(red pepper), C.frutescensL(cayenne pepper), andC.chinensis, C.bacctum, C.pubescens(chili gendot). However,theeconomicpotentialis a typeof chiliC.annuumandC.frutescensL. The purposeofthis study wastoknow theeffect of the useof plasticmulchoninsectabundanceMyzus persicaeoncropsandcayenne pepper. There arethree treatmentsbeing testedareplantingchiliusingblackplasticmulch(MH), a silverplasticmulch(MP) andplantingwithoutmulchorcontrol(K).The results showedthat theuse ofblack plasticmulchandsilverplasticmulchcannotpreventaphids andwhiteflyinchillicrop, however the presence ofblackplasticmulchandsilverplasticmulchcanreduceboththe insectpopulation. Key words :Cayenne Pepper,Myzus persicae, plastic mulch